An Analysis on the stylistic features of the “White Steamer” on the basis of word frequency statistics (Eurasian Journal of Philology Science and Education, 2022)
more detailed, in-depth and specific description of literary works using literary language and literary structures as the object of study, or to validate and justify readers’ interpretations of works using statistical data on textual features or retrieval data. The article is devoted to the generalization of the lexical features of the novel “White Steamer”, including the frequency of words, word length and thematic words of the novel. On this basis, the textual features of the novel “White Steamer” were analyzed, the themes and style of the novel by the author Aitmatov were revealed, and the main values expressed or reflected by the author in the novel were generalized. Corpus analysis of the text, of course, does not replace the evaluation of the literary work itself, but only provides evidence to support our understanding of the work. By applying corpus and statistical methods to the study of the linguistic style of literary works and writers, the study justifies the use of corpus stylistic and statistical methods to move the study of literary genres from reliance on intuition to reliance on objective and extensive statistical data. Statistical data can be used not only to prove previous conclusions, but also to identify some significant stylistic features that previously went unnoticed, which expands the horizons of research and significantly enhances the scientific and empirical nature of traditional literary research.